Augmented Reality for Solar System Learning - Mizanul Mashar; Ahmad Ali Hakam Dani; Muhlis Muhallim (Faculty of Engineering, Andi Djemma University, 2022)
AbstractAlong with the rapid development of smartphones and the absence of Solar System learning media in the case study of SMPN 3 RAMPI, for this reason, research, and development of Augmented Reality (AR) for Solar System Learning were made to make Android-based smartphones a media for learning the Solar System using Augmented Reality Technology and introducing Augmented Reality technology to students. The research method is the Research and Development (RD) method with the ADDIE (analysis, Design, Development, Implementation, evaluation) development model. The results of this study are: (1) This learning application is made using Blender software, Unity, and the Vuforia database, which helps facilitate the development process; (2) This learning application can already be applied in research locations and used as learning media that are more effective, efficient, and interactive so that they can help increase students' interest in learning; (3) The results of the application feasibility test questionnaire with usability-based questions distributed to selected respondents get a score of 90%, which is converted according to the feasibility percentage table, then the application is declared very feasibly.